2018
DOI: 10.1155/2018/6192483
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy by a Direct Aspiration First Pass Technique (ADAPT) in Ischemic Stroke: Results of Monocentric Study Based on Multimodal CT Patient Selection

Abstract: Introduction Mechanical thrombectomy with ADAP-technique of ischemic stroke has been reported as fast and effective. Aim of this study is to evaluate imaging criteria as possible predictors of stroke severity, therapeutic success, and outcome. Materials and Methods Patients (30) presenting from October 2015 to April 2017 with Emergent Large Vessel Occlusion of the anterior circulation were treated with ADAP-technique. 22 received also IV tPA; 8 underwent endovascular treatment only. Every patient was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Among the many outcome-related factors, time is emphasized as the patient's life channel. Some studies showed that the likelihood of favorable long-term outcomes decreased by 10% for each 30-minute extension of reperfusion 14,15 . The mean time from symptom onset to groin puncture in the unfavorable outcome group was significantly longer ( P < 0.05) in our study.…”
Section: Discussionsupporting
confidence: 40%
“…Among the many outcome-related factors, time is emphasized as the patient's life channel. Some studies showed that the likelihood of favorable long-term outcomes decreased by 10% for each 30-minute extension of reperfusion 14,15 . The mean time from symptom onset to groin puncture in the unfavorable outcome group was significantly longer ( P < 0.05) in our study.…”
Section: Discussionsupporting
confidence: 40%
“…In our data, FPE was significantly associated with smaller clot length (p = 0.007). Guzzardi et al also found that shorter clots were associated with better clinical outcomes in ADAPT [1]. This may be because longer surface area clots have larger friction and adhesion forces against the vessel, making them harder to retrieve and yielding worse thrombectomy outcomes [17].…”
Section: Discussionmentioning
confidence: 99%
“…We retrospectively collected the patient images, both intra-procedural 2D digital subtraction angiogram (DSA) and CT imaging (nCCT and CTA), and patient medical data from consecutive cases. Cases were excluded if (1) ADAPT was not used as first pass technique, (2) the occlusion was not originating from the M1 segment of the MCA, (3) intra-procedural 2D DSA was not available, (4) CT imaging was not available, (5) the available CT imaging had significant artifacts, poor contrast opacification (i.e., no opacification detected by expert neuroradiologist) or poor definition of the clot (i.e., no hyperdensity sign on nCCT or missing collaterals, resulting in ambiguous definition of clot, especially clot length) and ( 6) patient or treatment information was missing.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a longer duration of thrombectomy is an independent risk factor for sICH [23]. Multiple studies evaluating procedure duration report faster thrombectomy using aspiration than was observed with stent retrievers [9,16,24]. In contrast to most studies, the observational study by Nishi et al concluded that aspiration thrombectomy resulted in longer procedural times [17].…”
Section: Discussionmentioning
confidence: 99%